STORES SELLING APPLICATION SYSTEM NDAHNADHE PRODUCTION USING MICROSOST VISUAL BASIC.NET - Endah Wahyu Noprianti; Ristyawati, SKom., MMSI Ristyawati, SKom., MMSI (Jurnal Sistem Informasi, 2010)
On the application of sales and sales reports provide convenience to the user to inputthe data and then process them and produce desired outputs. In implementingpengolahaan data using computer applications using Microsoft Visual Basic.Net.Process sales at stores that previously Ndahnadhe Production still a lot of manualexperience difficulties in implementing the sales process, especially in making salesreports that are not effectively and efficiently. Therefore, the authors attempt to createa program ndahnadhe store sales system on production by utilizing the facilitiesavailable in Microsoft Visual Basic.Net to conduct the sale process and simplify thecheckout in the preparation of reports to be submitted to the leaders.